Creating a winning business formula (Cambridge University Press, 2002)
Part of a three-volume set on business strategy, performance, and competencies for manufacturers, this text presents an approach to reviewing current practices and developing long- term strategic plans. Coverage includes, for example, identifying customer product groups, defining business objectives, assessing current strategy, and embedding strategy making into the business culture.